When Much Means Less: Critical Reviews of Two "Nordic Noir" Novels by František Šmehlík - Hrtánek, Petr (Bohemica Olomucensia, 2024)
This article deals with two crime fiction books by František Šmehlík: the novel Slyšet jeleny zpívat (To Hear the Deer Sing, 2021) and the novel Šelma (The Beast, 2022). The critical reviewing especially focuses on the problem of transposition and modification of the "nordic noir" narrative model (typical settings, plots, characters) to the Czech fiction.
Keywords: Czech crime fiction; detective story; Nordic Noir; František Šmehlík; novels